Subfornical organ mediates pressor effect of angiotensin: Influence of nitric oxide synthase inhibitors, AT(1) and AT(2) angiotensin antagonist's receptors - Saad, Wilson Abrao [UNESP]; de Arruda Camargo, Luiz Antonio [UNESP]; Motta Siqueira Guarda, Ismael Francisco; Faria Brizola dos Santos, Talmir Augusto (Elsevier B.V., 2008)
We investigated the influence of voltage-dependent calcium channels and nitric oxide (NO) on angiotensin II (ANG II)-pressor effect injected into subfornical organ (SFO). The influence of NO on nifedipine antipressor action has also been studied by utilizing N(W)-nitro-L-arginine methyl ester (L-NAME) (20 mu g X 0.2 mu l(-1)) a nitric oxide synthase inhibitor (NOSI) and 7-nitroindazole (7-NIT) (20 mu g X 0.2 mu l(-1)), a specific neuronal nitric oxide synthase inhibitor (nNOSI). We have also investigated the role of losartan and PD123319, selective ANG II AT(1) and AT(2) receptor nonpeptide antagonists, in the pressor effect of ANG II and in the effect of L-NAME and 7-NIT, injected into the SFO. Adult male Holtzman rats (220 to 280 g) were anesthetized with ketamine (80 mg/kg(-1) of body weight) plus xylazine (7 mg/kg(-1) of body weight), placed in a stereotaxic apparatus (David Kopf model for rats), and implanted with cannula into the SFO. Direct mean arterial blood pressure (MAP) was recorded in conscious rats in a test cage, without access to food or water. The previously implanted catheter into femoral artery was connected to a Statham (P23 Db) pressure transducer (Statham-Gould, Valley View, OH) coupled to a multichannel recorder (PowerLab Multirecord). MAP increased after ANG II injection. Pre-treatment with nifidipine (50 mu g X 0.2 mu l(-1) or 100 mu l(-1) X 0.2 mu l(-1)) followed by 25 pmol X 0.2 mu l(-1) of ANG II, decreased ANG H-pressor effect. L-NAME and 7-NIT increased the elevation in MAP induced by ANG II, which was blocked by the prior injection of nifedipine. The AT(1) angiotensin antagonist losartan injected into the SFO blocked the effect of ANG II and the effects of L-NAME and 7-NIT while PD 123319 did not. These results provide evidence that ANG II-pressor effect is influenced by nitrergic pathways that utilize L-type calcium channels in the SFO. J Am Soc Hypertens 2008;2(5): 326-331. (C) 2008 American Society of Hypertension. All rights reserved.
Keywords: Angiotensin II; calcium channel; central nervous system; blood pressure